Padrões espaço-temporais da mortalidade relacionada à co-infecção tuberculose e HIV/AIDS no Brasil, 2000 - 2011 - Lima, Mauricélia da Silveira (2015)
The co-infection Mycobacterium tuberculosis and HIV is an important public health problem with high morbidity and mortality burden in the world and in Brazil. This study aimed to characterize the spatial and temporal patterns of mortality related to this co-infection in the country from 2000 to 2011. Descriptive and analytical study using secondary data obtained from the Health Information System Ministry of Health (SIM/DATASUS/MS). In study ecological time series and spatial analysis were integrated analysis of temporal and spatiotemporal patterns trends in risk areas identified for mortality related to co-infection TB and HIV/AIDS in Brazil. Geographic regions, Federative Units and municipalities were the units of analysis. We calculate specific mortality rates and the proportional mortality for the time trends analysis using the joinpoint regression model. We investigated the factors associated with death and described the causes of death associated with co-infection. For spatial autocorrelation analysis and risk areas identification, we used the following methods: global Moran, local Moran, and spatial analysis scan. We analyzed all deaths in Brazil from 2000 to 2011 in which tuberculosis (TB) and HIV/AIDS were mentioned in the same death certificate(DO). In the period 2000-2011, there were a total of 12,491,280 deaths in Brazil, 19 815 of these related to co-infection (HIV/AIDS as the underlying cause in 98.6% and TB in 0.03%).The average annual rate of adjusted mortality rate was 0.97/100,000 population and the proportional mortality was 0.16%. During the study period we verified a downward trend(AAPC: 1.6%; 95% CI: -2.3 to -0.8), with significant inter-regional variation: increase in North (AAPC: 5.9%, 95% CI: 2.4 to 9.6), Northeast (AAPC: 5.7%; 95% CI: 3.5 to 7.9) and Central West (AAPC: 3.6%; 95% CI: 0.2 to 7.1) regions, reduction in the Southeast (AAPC: - 4.8%; 95% CI: -6.1 to -3.6), and stabilization in the South. We identified as risk factors for coinfection: male sex, age over 20 years, residence in the Southeast or South region, and white or brown race/color. Conditions related to the natural history of both diseases, especially respiratory diseases and the other co-infections caused by bacteria, viruses and protozoa were the main causes of death associated with TB and HIV/AIDS co-infection, corresponding to 60% of the total mentions in DOs. The spatial analysis identified one spatial aggregate (cluster) with high risk for mortality related to co-infection involving a state in the South region and 4 additional smaller clusters covering the North, Northeast and Southeast regions. Despite the slight decline in mortality related to this co-infection, there are a significant inter-regional differences and a wide geographic distribution in Brazil. The strategic and effective integration between national, state and local TB and HIV/AIDS control programs is related to the recognition of different contexts of risk and vulnerability. These approaches are determinant to implement appropriate and specific control measures. We emphasize the importance of epidemiological monitoring of mortality indicators related to the TB and HIV/AIDS coinfection in Brazil, particularly in high-risk areas.